Visual Awareness: Enabling Iterative Thinking through Photography - Ricardo Lopez-Leon (ITB Journal Publisher, LPPM ITB, 2020)
This paper presents research results that aid in understanding how photography can become a tool for iterative thinking as a mode of reflection. The research was conducted in three phases. The first consisted of a specific task: after reading assigned materials from different sources, PhD students had to take a photograph as a visual reading-report. In the second phase, all the created images were presented and discussed during class. In the last stage, the students talked about their experience through in-depth interviews. The findings showed that visual awareness linked observation and reflection at the same time, since the students were continually looking for ordinary objects to carry new meanings that were relatable to specific arguments and ideas expressed in the reading materials. Hence, visual awareness is understood in this paper as a mode of visual perception that enables a process of thinking iteratively about a particular topic. The photographic camera was identified as a thinking tool that could be a valuable device to incorporate into educational activities. Finally, in addition to practicing iterative thinking, students expressed feeling engaged and motivated, enjoying this activity, and embracing the challenge.